Upstream interventions to promote oral health and reduce socioeconomic oral health inequalities: a scoping review protocol - Richard G Watt; Eleanor R Dawson; Michelle Stennett; Blánaid Daly; Lorna M D Macpherson; Paul Cannon (BMJ Open)
Introduction Improving oral health and reducing oral health inequalities is an important global health priority. ‘Upstream interventions’ are a vital part of the collective effort to reduce oral disease burdens, however it is a rather nebulous term. Furthermore, there is little evidence on the effectiveness, impact and sustainability of upstream interventions that have focused on oral health and wider public health measures that impact on oral health. The aim of this scoping review is to systematically map and synthesise evidence on the effectiveness, impact and sustainability of upstream interventions on population oral health and reducing socioeconomic oral health inequalities.Methods and analysis This scoping review will be conducted in accordance with the Joanna Briggs Institute methodology and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews checklist. A detailed search strategy will be used to conduct a comprehensive search of electronic databases: Scopus, Embase and MEDLINE, PsycINFO and CINAHL, ASSIA and Cochrane Database of Systematic Reviews. A search of grey literature will also be completed to identify relevant dissertations, governmental reports and evaluations of implemented policies. Identification and extraction of data will be performed by two pairs of reviewers. Oversight and feedback will be provided by an independent expert advisory group.Ethics and dissemination This study will review published and available grey literature and does not require an ethics review. The scoping review protocol has been registered with the Open Science Framework. The final report will be circulated and disseminated through publication and feed into the work of the ongoing Lancet Commission on Oral Health. Due to the policy relevance of this work, discussions will take place with key stakeholders regarding the implications of the findings for future policy development.